Perspectives on Heterogeneous Photochemistry. Issue 5 (18th August 2014) - Friend, Cynthia M.
Abstract Heterogeneous photochemistry has a potentially important role in production of energy, in environmental remediation and in sustainable production of chemicals. Photochemical efficiency depends on both materials properties and the desired chemical reaction that is promoted through creation of an excited state. A detailed understanding of the interplay between materials properties and reactivity requires a molecular‐scale approach that determines the elementary steps in the overall process. This personal account summarizes the role of defects in determining the photochemical and thermal reactions on rutile titania, a model for semiconductor metal oxide photocatalysts that defects, e.g., Ti interstitials present in the subsurface region, and O adatoms on the surface, have a substantial impact on the efficiency for photochemical conversion through modification of molecular binding and also through likely modification of charge carrier dynamics. Design of materials must include engineering of the optical and electronic properties of the semiconductor photocatalyst, and understanding of the key photochemical steps involved in specific processes to ensure proper alignment of their electronic states with the band structure of the material. Thus, fundamental surface science studies and development of time‐dependent theoretical methods that map out the reaction mechanism for photochemical processes on materials with controlled composition and structure are critical.